2019
DOI: 10.1108/ijhma-07-2018-0052
|View full text |Cite
|
Sign up to set email alerts
|

Developer constraints on housing supply in urban Ghana

Abstract: Purpose This study aims to document the major underlying forces prohibiting housing development in urban Ghana. Previous studies in Ghana have not empirically examined these constraints, but an empirical examination of these factors would help to formulate proper policies to address the housing shortage problems in Ghana. This paper fills this gap. Design/methodology/approach Using a purposive sampling technique, the authors surveyed the chief executive officers (CEOs) of private real estate development comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Generally, Ghanaian technical universities lack basic facilities, including accommodation for their staff, which promotes the drift of their staff to traditional universities with better infrastructure. Accessing affordable and decent accommodation in Ghana, particularly in urban locations, has been challenging because of the housing deficit (Owusu-Ansah et al, 2019). Therefore, management of these technical institutions support staff to access appropriate accommodation as part of their retention strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, Ghanaian technical universities lack basic facilities, including accommodation for their staff, which promotes the drift of their staff to traditional universities with better infrastructure. Accessing affordable and decent accommodation in Ghana, particularly in urban locations, has been challenging because of the housing deficit (Owusu-Ansah et al, 2019). Therefore, management of these technical institutions support staff to access appropriate accommodation as part of their retention strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Governance, which supports participation of the private sector and local community in decision-making influence real estate development and sustainability [33]. Government can create an "enabling environment" for private sector investment and accelerate real estate development [34].…”
Section: Governancementioning
confidence: 99%
“…Additionally, inadequate land policies and poor consultative processes result in inefficiencies in the process of making land available for housing development [40]. The difficulty in accessing development funds, underdeveloped mortgage market and high interest rates, land tenure arrangements, lengthy building permit/warrant approval and land acquisition and registration processes discourage real estate investments in Ghana [33]. Similarly, sound financial and economic structure, stability of the economy, restrictions and regulations on investors and legal regulation are the most important issues affecting the market attractiveness in Southeast Asian cities [41].…”
Section: Economic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Ogunnaike (2017) categorised these factors into the three groups: socio-cultural, economic and political and institutional factors. Owusu-Ansah et al (2019) found that real estate practitioners consider housing supply problems to be driven mainly by formal and informal institutional factors such as land tenure arrangements and lengthy procedure for acquiring property.…”
Section: Factors Influencing Homeownershipmentioning
confidence: 99%